Reading Habits and Its Effect on Academic Writing Skill: A Study of Master Degree Students - khoirunnisa khoirunnisa; Ida Dwi Safitri ((JELE) Journal Of English Language and Education, 2018)
Nowadays, students centered became a popular strategy in English Language Teaching (ELT). Teacher preferred to become a facilitator in the learning activity. Thus, as the learner, students should do an activity that had a big effect on their learning process. Reading was one of the important activity that had a great advantage to increase students writing skill. They should take reading as their habitual activity to get a significant improvement of learning achievement. In the context of higher education, reading activity was a basic requirement to start an activity in academic work such as writing a scientific journal. Through reading, they could get new information from the text. Then, it could be synthesized, evaluated, and implicated as the prior knowledge or supporting information in their writing. The aim of this study was to examine the reading habit of master degree students’ and its effect on their academic writing skill. Twenty students from the master degree of Sebelas Maret University, Indonesia were selected to participate in the study.The data collected through an e-survey analyzed qualitatively. The finding indicated reading habit was crucial for students’ academic writing skill. Furthermore, the conclusion discussed the implication of the finding in relation with teaching advanced learner.Nowadays, students centered became a popular strategy in English Language Teaching (ELT). Teacher preferred to become a facilitator in the learning activity. Thus, as the learner, students should do an activity that had a big effect on their learning process. Reading was one of the important activity that had a great advantage to increase students writing skill. They should take reading as their habitual activity to get a significant improvement of learning achievement. In the context of higher education, reading activity was a basic requirement to start an activity in academic work such as writing a scientific journal. Through reading, they could get new information from the text. Then, it could be synthesized, evaluated, and implicated as the prior knowledge or supporting information in their writing. The aim of this study was to examine the reading habit of master degree students’ and its effect on their academic writing skill. Twenty students from the master degree of Sebelas Maret University, Indonesia were selected to participate in the study.The data collected through an e-survey analyzed qualitatively. The finding indicated reading habit was crucial for students’ academic writing skill. Furthermore, the conclusion discussed the implication of the finding in relation with teaching advanced learner.